ANALISIS KINERJA KEUANGAN PERBANKAN SYARIAH DENGAN METODE SHARIA CONFORMITY AND PROFITABILITY (SCnP) - Welly Aprida Wahyuni; Mursyid Mursyid; Angrum Pratiwi (Indonesian Scientific Journal of Islamic Finance, 2023)
The assessment of the financial performance of Islamic banking is mostly still measured by conventional measuring instruments. Where the measuring instrument only focuses on financial measurement while Islamic banking is a banking institution that is run using sharia principles, but does not ignore the financial side. The purpose of this study was to measure the financial performance of Islamic banking using the Sharia Conformity and Profitability (SCnP) method, which is a more complex performance measurement because it combines two inseparable assessment orientations, namely sharia and finance. This research is a descriptive quantitative research. The population in this study is the financial statements on sharia banking statistics published by OJK using saturated sampling as the sample of this study. The variables of this study are Sharia Conformity and Profitability. The types of data used are secondary data and the data collection technique in this study is documentation. The results of this study show the financial performance of Islamic banking, at the quadrant level showing SCnP results during the 2017-2021 period BUS in Indonesia are in four quadrants, namely the Lower Left Quadrant, which has sharia conformity and low profitability. Upper Left Quadrant, namely with low sharia compatibility and high profitability. Upper Right Quadrant, has sharia compatibility and high profitability. And the Lower Right Quadrant, where sharia conformity is high but the profitability is low. And the financial performance of UUS in Indonesia is in three quadrants, namely Lower Left Quadrant, Lower Right Quadrant and Upper Right Quadrant during the 2017-2021 period. Whereas in BPRS during the 2017-2021 period financial performance was in three quadrants namely Lower Left Quadrant Upper Left Quadrant and Lower Right Quadrant.